2019
DOI: 10.3174/ajnr.a6323
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-Enhanced MR Imaging of Nonenhancing T2 High-Signal-Intensity Lesions in Baseline and Posttreatment Glioblastoma: Temporal Change and Prognostic Value

Abstract: BACKGROUND AND PURPOSE: The prognostic value of dynamic contrast-enhanced MR imaging on nonenhancing T2 high-signal-intensity lesions in patients with glioblastoma has not been thoroughly elucidated to date. We evaluated the temporal change and prognostic value for progression-free survival of dynamic contrast-enhanced MR imaging-derived pharmacokinetic parameters on nonenhancing T2 high-signal-intensity lesions in patients with glioblastoma before and after standard treatment, including gross total surgical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…35 In addition, the volume transfer constant in the NER could be a potential prognostic imaging biomarker in GBM. 36,37 Blood perfusion in the tumor and surrounding tissue may be related to the chemotherapeutic agent in drug delivery. 38 Yoo et al 39 reported that an enhancing lesion with a low volume transfer constant and v e (volume of extravascular extracellular space) was more likely to progress because of its low permeability or leakiness of the BBB, in which the delivery of TMZ to viable tumor cells might be less effective during standard treatment.…”
Section: Figmentioning
confidence: 99%
“…35 In addition, the volume transfer constant in the NER could be a potential prognostic imaging biomarker in GBM. 36,37 Blood perfusion in the tumor and surrounding tissue may be related to the chemotherapeutic agent in drug delivery. 38 Yoo et al 39 reported that an enhancing lesion with a low volume transfer constant and v e (volume of extravascular extracellular space) was more likely to progress because of its low permeability or leakiness of the BBB, in which the delivery of TMZ to viable tumor cells might be less effective during standard treatment.…”
Section: Figmentioning
confidence: 99%
“…We specified the extent of resection as maximal resection at least (i.e. including complete resection), because we focused to investigate the recurrence pattern when no measurable residual enhancing leseions were left after surgery, excluding the recurrence from measurable residual tumor 26 , 50 .…”
Section: Methodsmentioning
confidence: 99%
“…As a result, our study population was categorized into disease recurrence group ( n = 125), and non-recurrence group ( n = 67). The progression free survival (PFS) was defined as the interval between the initial diagnosis by MRI examination and the assessment of disease progression, or the last follow-up if the patient had no evidence of disease in the last follow-up 50 .…”
Section: Methodsmentioning
confidence: 99%
“…We speci ed the extent of resection as maximal resection at least (i.e. including complete resection), because we focused to investigate the recurrence pattern when no measurable residual enhancing leseions were left after surgery, excluding the recurrence from measurable residual tumor 33,34 .…”
Section: Patientsmentioning
confidence: 99%
“…As a result, our study population was categorized into disease recurrence group (n=125), and non-recurrence group (n=67). The progression free survival (PFS) was de ned as the interval between the initial diagnosis by MRI examination and the assessment of disease progression, or the last follow-up if the patient had no evidence of disease in the last followup 33 .…”
Section: Patientsmentioning
confidence: 99%